Development of Design Parameters for the Concentrator of Parabolic Dish (PD) Based Concentrating Solar Power (CSP) under Malaysia Environment - Ab Ghani, Mohd Ruddin; Gan, Chin Kim; Affandi, Rosnani (AENSI Publisher, 2014)
Concentrating Solar Power (CSP) technologies has the ability to harness solar energy for producing the electricity. The development becomes increasingly important for economies in many countries, especially in the regions that is hot, dry and received excellent solar radiation. Meanwhile, among the CSP technologies, Parabolic Dish (PD) system has demonstrated a high thermal efficiency and the implementation of PD concentrator will result in sustainable energy generation with emission free operation. However, PD based CSP technology is still an emerging industry in Malaysia with no operation plant installed so far. It still needs thorough review before developing the PD technologies under the Malaysia tropical environment. Therefore a Matlab Simulink is used in this work to design the concentrator for the PD 1kW system under Malaysia environment. This paper elaborates the methodology utilized to develop the concentrator for the PD 1kW system and outlines the parameter that's used for increasing the efficiency of PD based CSP under Malaysia tropical environment. From the simulation result, it is suggested to used 3.7 meters for the concentrator diameter and aluminium as the reflective material for the concentrator. As a conclusion the size and the reflective material for the concentrator are essential. Therefore, it should be taken into account before developing the geometric parameters for PD concentrator under Malaysia environment.